Proximate Composition of Some Common Alternative Flour as Fish Feed Ingredient - Herdiyanti, Arrum Nurjannah; Nursyam, Happy; Ekawati, Arning Wilujeng (Graduate School, Universitas Brawijaya, 2018)
Indonesia has very large territorial water, so it supports the development of the economy in the field of fisheries, one of which is through aquaculture. Recently fish meal has become the most expensive protein ingredient in aquaculture feeds. We aim to proximately analysis of some common alternative flour as fish feed ingredient i.e. fish flour, shrimp head flour, soybean flour, and bran flour to get best-recommended flour for type cultured fish. Fish flour, shrimp head flour, soybean flour, and bran flour was purchased from the fish farmer in Malang who use alternative fish feed flour for their aquaculture. Proximate analysis carried out by protein content, Moisture content, Fat and Fiber. Proximate analysis was conducted in the Fishery Products Engineering laboratory, Brawijaya University on April 2018. The results showed that shrimp head flour had higher protein content than others flour that is about 48.71%, fat and carbohydrate content about 7.99%, and 18.34% respectively. Soybean flour contains protein, fat and carbohydrate about 31.29%, 20.75%, and 30.45% respectively. Carnivorous fish culture can use high protein flour as an alternative ingredient for feed such as fish flour and shrimp head flour; balance proximate composition for omnivorous fish cultures such as soy flour and high carbo flour such as bran flour for herbivorous fish culture.Keywords: Bran flour, Shrimp head flour, Soybean flour, Proximate analysis.